The Parish Catechesis in the Archdiocese of Warmia – Current State (October 2012) and Challenges in the Future - Bielinowicz, Adam (Studia Warmińskie, 2013)
The author of the article uses statistical data to present various forms of parish catechesis that are conducted today in the Archdiocese of Warmia. Then, referring to both the documents of The First (XIV) Synod of the Archdiocese of Warmia and subject literature, the author reflects on parish catechesis, which is necessary to make a parish a proper and successful place of adult, youth and children catechesis.